2019
DOI: 10.17503/agrivita.v41i2.2162
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Distribution and Abundance of Scale Insect Associate with Several Clones of Durian (Durio zibethinus Merr.)

Abstract: Durian contributes a high economic value in agribusiness of horticultural product. However, recently the attack of scale insect has devastated most of pre-production trees in Indonesia. A research with objective to know the basic information about the correct species, distribution and population abundance was done at Aripan Research Station of Indonesian Tropical Fruits Research Institute from July to August 2018. A proper identification and observation method were used to know the species identity, distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Sunaryo (2003) reported that the main pests in sugarcane are shoot borer (Scirpophaga nivella), stem borer (Chilo auricilius), and scale insect (Aulacaspis tegalensis). The genus of Aulacaspis comprises large number of species which has been reported to be a pest in many cultivated plants (Takagi & Faferi, 2009;González-Gómez et al, 2016;Affandi et al, 2019). In this recent decades, the invasion of scale insects in sugarcane plantation in Sumatera Island is floating.…”
Section: Introductionmentioning
confidence: 99%
“…Sunaryo (2003) reported that the main pests in sugarcane are shoot borer (Scirpophaga nivella), stem borer (Chilo auricilius), and scale insect (Aulacaspis tegalensis). The genus of Aulacaspis comprises large number of species which has been reported to be a pest in many cultivated plants (Takagi & Faferi, 2009;González-Gómez et al, 2016;Affandi et al, 2019). In this recent decades, the invasion of scale insects in sugarcane plantation in Sumatera Island is floating.…”
Section: Introductionmentioning
confidence: 99%